Identification of Emerging Human-Pathogenic Pythium insidiosum by Serological and Molecular Assay-Based Methods - Vanittanakom, Nongnuch (American Society for Microbiology, 2004)
Pythium insidiosum is a pathogen that causes disease in both animals and humans. Human infection is rare; however, when it does occur, most patients, especially those having underlying hemoglobinopathy syndromes, such as thalassemia, exhibit a severe form. We identified four isolates of P. insidiosum. Two were recovered from tissue biopsy specimens from thalassemic and leukemic patients, one was derived from brain tissue from a thalassemic patient, and another was isolated from a corneal ulcer from a fourth patient. Western blotting and an enzyme-linked immunosorbent assay (ELISA) were performed with a serum sample derived from one thalassemic patient. The methods used to identify the P. insidiosum isolates were based on morphology, nucleic acid sequencing, and a PCR assay. To confirm the identification, portions of the 18S rRNA genes of these four isolates were sequenced. The sequences were shown to be homologous to previously described P. insidiosum DNA sequences. In addition, PCR amplification of the internal transcribed spacer region specific for P. insidiosum was positive for all four isolates. The ELISA with the serum sample from the thalassemic patient gave a positive result from a serum dilution of 1:800. Finally, Western immunoblotting with this serum sample showed positive immunoglobulin G recognition for proteins of 110, 73, 56, 42 to 35, 30 to 28, 26, and 23 kDa. The results of this study show that both molecularly based diagnostic and serodiagnostic techniques are useful for the rapid identification of human pythiosis. The predominant antigens recognized by Western blotting may be useful in the development of a more sensitive and specific diagnostic tool for this disease.